Sistem Informasi Data Perkara Tindak Pidana Khusus Pada Kejaksaan Tinggi Aceh - Fikri, Muntazul; Imilda; Syarifuddin (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
The Aceh High Prosecutor's Office is one of the most important parts of the Unitary State of the Republic of Indonesia's High Prosecutor's office. The Aceh High Prosecutor's Office is the